Evaluating Sarconesiopsis magellanica blowfly-derived larval therapy and comparing it to Lucilia sericata-derived therapy in an animal model (2016)
Larval therapy is used as alternative treatment for hard-to-heal chronic and infected wounds. Lucilia sericata is the most used blowfly species. However, it has been shown recently that Sarconesiopsis magellanica larval excretions and secretions have potent antibacterial activity; this blowfly belongs to the Calliphoridae family.The present work has dealt with evaluating larval therapy using S. magellanica on wounds induced in diabetic rabbits and its action was compared to the effect induced by L. sericata. Twelve New Zealand White rabbits (. Oryctolagus cuniculus) were used; they were divided into 4 groups, the first two being treated with larval therapy derived from both aforementioned necrophagous blowflies, an antibiotic was used in the third and the fourth was used as control. All the animals were wounded on the back and infected with Pseudomonas aeruginosa and Staphylococcus aureus.Samples of the secretion from each animal's infected wound were taken and sown on blood agar. The colony forming units were then counted. The PUSH scale was used for the macroscopic evaluation of the wounds.Bacterial control was encountered 48. h post-treatment in the treatments involving larval therapy and to a lesser extent with the antibiotic. Likewise, wound debridement was quicker and more efficient with larval therapy compared to the antibiotic group; however, wound closing time was 23 days in all treatments. The group treated with S. magellanica larvae had relatively quicker evolution until the proliferation phase and the start of maturation, even though there were no significant differences between both blowfly species evaluated here regarding treatments by the end of the treatment period.The present study has validated the diabetic rabbit model for inducing chronic wounds regarding larval therapy and has likewise confirmed the effectiveness of S. magellanica-derived larval therapy as an alternative for curing and healing wounds. © 2015 Elsevier B.V.